EFFECT OF SILVER NANOPARTICLES SYNTHESIZED USING LEAVES EXTRACT OF OLIVE ON HISTOPATHOLOGICAL AND CYTOGENETIC EFFECTS IN ALBINO MICE - Al-taee, E. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted to examine the possible effects of Ag-NPs synthesized using the olive leaf extract on histopathology and cytogenetic effect in mice. A total of thirty albino mice aged two months were divided into five treatment groups as follows: Group 1: served as control was administrated orally with 0.3 mg/kg bw of normal saline; Group 2 and 3 were administrated orally with varying doses of Ag-NPs synthesized on olive leaf extract (10 and 100 mg/kg bw, respectively) for 30 days; Group 4 and 5 were administrated orally with olive leaf crude extract (300 and 1000 mg/kg bw, respectively) for 30 days. At the end of the experimental period, the detection of possible chromosomal aberrations in blood samples and histopathology (liver, spleen, kidney, uterus, and testes) were carried out. Statistically significant differences (P